DETERMINING THE RECOVERY TIME OF THE FIRE-SAFE CONDITION OF HYDROGEN STORAGE AND SUPPLY SYSTEMS - Abramov, Yu.; Kryvtsova, V.; Mykhailiuk, A. (Municipal economy of cities. Series: «Economy science», 2024)
The fire prevention system can function in passive or active modes. In active mode, such a system implements a set of measures aimed at restoring the fire-safe state of the hydrogen storage and supply system after it is in a fire-hazardous state. The authors consider variants of its functioning for a highly reliable fire prevention system. The first option has the reliability of the fire inspection, which is equal to one, and the second option has the reliability of the fire inspection, which is different from one. Using graphs of the states of the hydrogen storage and supply system, we constructed systems of Kolmogorov equations and derived expressions for the probabilities of finding this system in the corresponding states. The article shows that the time to restore the fire-safe state of the hydrogen storage and supply system in the first variant should not exceed the probability of its being in a fire-hazardous state, reduced to the unit of the intensity of the transition of this system from a fire-safe state to a fire-hazardous state. In the second option, the time to restore the fire-safe state of the hydrogen storage and supply system increases following the law described by a hyperbola of the first order, the argument of which is the reliability of the fire safety inspection of such a system. We have obtained an expression for the reliability of the functioning of the fire prevention system focused on ensuring the fire safety of hydrogen storage and supply systems. We show that the reliability of the functioning of such a prevention system depends significantly on the reliability of the fire-engineering inspection of the hydrogen storage and supply system. We have also derived an expression for the time to restore the fire-safe state of the hydrogen storage and supply system that is determined a priori by the reliability of the fire prevention system functioning, the reliability of the fire inspection, and the intensity of the transition of the hydrogen storage and supply system from the fire-safe to the fire-hazardous state.